2021
DOI: 10.3389/fmed.2021.644195
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Loading for Refractory Septic Shock: A Preliminary Analysis of a Case Series

Abstract: Background: Vasopressin is one of the strong vasopressor agents associated with ischemic events. Responses to the administration of vasopressin differ among patients with septic shock. Although the administration of a high dose of vasopressin needs to be avoided, the effects of bolus loading have not yet been examined. Since the half-life of vasopressin is longer than that of catecholamines, we hypothesized that vasopressin loading may be effective for predicting responses to its continuous administration.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
9
0
3
Order By: Relevance
“…Often the response to vasopressor agents is not taken into account when defining these subphenotypes, even though different trajectories are associated with different outcomes (156). Selecting patients responding to vasopressin may be achieved with the use of a loading dose (157), but this is less likely to occur with other vasopressor agents. It also needs to be determined whether perfusion targets should be adjusted to the phase of sepsis (158).…”
Section: Resultsmentioning
confidence: 99%
“…Often the response to vasopressor agents is not taken into account when defining these subphenotypes, even though different trajectories are associated with different outcomes (156). Selecting patients responding to vasopressin may be achieved with the use of a loading dose (157), but this is less likely to occur with other vasopressor agents. It also needs to be determined whether perfusion targets should be adjusted to the phase of sepsis (158).…”
Section: Resultsmentioning
confidence: 99%
“…This is analogous to broad-spectrum and early antimicrobials in suspected and confirmed sepsis. Some studies pointed out that whether vasopressin was used or not could be based on the hemodynamic response after 1 U bolus vasopressin is administered [ 28 ] or a machine learning prediction model [ 29 ]. On the contrary, Jakowenko et al found that early vasopressin initiation was not associated with responsiveness at 4 h post-catecholamine initiation, suggesting that it may be reasonable to implement the 2021 SSC guidelines [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that the half-life of the drug is 10 to 35 min, requiring a longer time to reach steady state and adequate pharmacological response. For this reason, bolus administration is often used in medical practice due to the severity of refractoriness cases (Nakamura et al 2021).…”
Section: Discussionmentioning
confidence: 99%